2006
DOI: 10.1615/intjmultcompeng.v4.i1.110
|View full text |Cite
|
Sign up to set email alerts
|

Trans-scale Coupling in Multiscale Simulations

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2006
2006
2006
2006

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 13 publications
(18 reference statements)
0
2
0
Order By: Relevance
“…However, as shown in figure 9, the catastrophic rupture cannot be predicted only from the σ -ε curve. Actually, from our computations, we found that the stress redistribution resulting from the damage interaction plays a critical role in the catastrophic rupture, which we will report in another paper [18] with more computations to clarify the significant mechanism governing the trans-scale phenomenon.…”
Section: Numerical Examplementioning
confidence: 53%
“…However, as shown in figure 9, the catastrophic rupture cannot be predicted only from the σ -ε curve. Actually, from our computations, we found that the stress redistribution resulting from the damage interaction plays a critical role in the catastrophic rupture, which we will report in another paper [18] with more computations to clarify the significant mechanism governing the trans-scale phenomenon.…”
Section: Numerical Examplementioning
confidence: 53%
“…Recent works in the study of multiscale coupling (BAZANT and CHEN, 1997;WANG et al, 2004;RONG et al, 2006) suggest that damage evolution and rupture of solid can be regarded as a trans-scale process in a wide range of spatiotemporal scales. Traditionally, researchers working on computational simulations concentrated on bringing practical details into their models, but ignored various spatial scales inherent in heterogeneous media.…”
Section: Introductionmentioning
confidence: 99%